Cuban Connection: Regional Role for Florida's Manatees - Alvarez-Alemán, Anmari; Austin, James D.; Jacoby, Charles A.; Frazer, Thomas K. (Frontiers in Marine Science, 2018)
The status of the West Indian manatee [Trichechus manatus (Linnaeus, 1758)] remains enigmatic. The International Union for Conservation of Nature classifies the species as “Vulnerable” and the two subspecies [T. m. manatus (Linnaeus, 1758) and T. m. latirostris (Harlan, 1824)] as “Endangered.” The U.S. Fish and Wildlife Service now classifies West Indian manatees as “Threatened” primarily due to increased numbers of T. m. latirostris. Fully resolving the status of the species will require a better understanding of its population biology throughout the broader Caribbean region, especially the form and strength of genetic and demographic connections. Genetic studies indicate limited interbreeding among recent generations of groups of manatees separated by unsuitable coastal habitat or large expanses of open water, such as the Florida Straits. However, documentation of two, independent immigrations from Florida to Cuba within one generation raises the possibility of important demographic connections, especially if the number of manatees in Cuba is small. In addition, these events may foreshadow a change in the role that Florida’s manatees play in effective conservation of T. manatus throughout its Caribbean range, with the potential for further connections as numbers of manatees in Florida increase and the availability of suitable habitat and food decreases.